Angioimmunoblastic T-cell Lymphomas With the RHOA p.Gly17Val Mutation Have Classic Clinical and Pathologic Features. (March 2016) - Ondrejka, Sarah L.; Grzywacz, Bartosz; Bodo, Juraj; Makishima, Hideki; Polprasert, Chantana; Said, Jonathan W.; Przychodzen, Bartlomiej; Maciejewski, Jaroslaw P.; Hsi, Eric D.
Abstract : Angioimmunoblastic T-cell lymphoma (AITL) is a nodal-based mature T-cell lymphoma with distinctive clinical symptomatology and histology. Research into its pathogenesis supports a cellular derivation from follicular helper T cells and overexpression of genes related to B cells, follicular dendritic cells, and vascular growth. Recently, a novel recurring somatic mutation in RHOA, encoding p.Gly17Val, was discovered in nearly 70% of AITLs and in a smaller proportion of peripheral T-cell lymphomas, not otherwise specified (PTCL-NOS). We investigated a series of AITLs to compare RHOA mutated with wild-type case for clinicopathologic differences. Targeted exome and Sanger sequencing was performed on 27 AITLs and 10 PTCL-NOS. The RHOA G17V mutation was identified in 63% of the AITL cases and in none of the PTCL-NOS cases. The median variant allelic frequency was 14%, with a range of 0.4 to 50% in positive cases. RHOA G17V-mutated cases had a significantly higher incidence of splenomegaly and B symptoms at diagnosis, but there was no difference in overall survival between mutated and wild-type subgroups. Cases with the RHOA G17V mutation had a significantly higher mean microvessel density ( P <0.01) and expressed a greater number of follicular helper T-cell markers ( P <0.05) than wild-type cases. RHOA G17V is present in a significant proportion of angioimmunoblastic lymphomas and is associated with classic pathologic features of AITL. Additional studies are needed to provide a biological or functional link between altered RHOA function and these pathologic features.